Acronyms and synonyms in medical imaging - Allison, David J; Strickland, Nicola (Isis Medical Media, 1996)
The Royal Post graduate Medical School, Hammersmith, London. Reference of acronyms, and synonyms utilized in clinical imaging settings. For practitioners, nurses, and medical secretaries. Includes a brief definition and cross-references where possible. 5 contributors, 1 U.S.
Keywords: radiologie; Dictionaries, Medical as Topic; lékařská informatika; lékařské slovníky jako téma; Radiology; radiologie, nukleární medicína a zobrazovací metody